Capital Structure Adjustment Speed in Indonesia: Does Sharia Compliance Matter? - Arum Pujiastuti; Rizki Dini Shandra Yunita; Yuni Astuti; Saefudin Saefudin (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Leverage Speed of Adjustment (henceforth SOA) has previously been studied by researchers; however, the examination of its connection with sharia law has been overlooked. The majority of the literature currently in circulation comes from the Middle East and North Africa (MENA) region and Malaysian markets, so its implications for businesses in Indonesia may not be applicable given local regulations and cultural norms. This study investigates the distinction in the debt levels and the SOA of firms in Indonesia based on compliance to sharia law. The Two-step Generalized Method of Moment (GMM) model was used to calculate the SOA in the leverage model. We discover that sharia compliance plays a role in stimulating the Indonesian firm’s level of debt and leverage SOA. To put it more precisely, sharia firms use less debt and have a slower SOA than conventional firms. Overall, Indonesian firms implement the dynamic trade-off theory in their leverage framework. Instead of relying on conventional debt, which is only available at certain levels, sharia firms must issue Islamic debt instruments to accelerate the speed of adjustment. Even after a robustness test using various sharia compliance approaches, our results remained consistent.